Maternal mind-mindedness: stability over time and consistency across relationships. Issue 4 (3rd July 2016) - Illingworth, Gaby; MacLean, Morag; Wiggs, Luci
Abstract: Maternal mind-mindedness has been described both as a cognitive-behavioural trait and as a relational construct. This study assessed stability over time and consistency across relationships of maternal mind-mindedness in relation to preschool and primary school siblings and compared representational and interactional mind-mindedness. Mothers with two children between 2½ and 10 years were assessed twice, nine months apart ( N  = 32 at Time 1; N  = 30 at Time 2). Representational mind-mindedness for a partner/friend was also assessed twice. Mothers' representational mind-mindedness showed temporal stability but was inconsistent across relationships with two children and a partner/friend. Conversely, mothers' interactional mind-mindedness was stable and highly consistent across relationships with two children. This supports the possibility that mothers' interactional mind-mindedness is trait-like, while findings are equivocal for representational mind-mindedness. Representational mind-mindedness and interactional mind-mindedness were unrelated in this preliminary study, suggesting that these measures of maternal mind-mindedness were not equivalent for this age group.